Young children, parents and professionals : enhancing the links in early childhood - Henry, Margaret, 1931- (Routledge, 1996)
As early year education and very early child care increase, parents and professionals face many difficult questions. What are the effects of early education on children? Are parents fulfilling their roles? What should teachers' roles be? Seldom asked are more basic questions: What are the fundamental needs of young children? Or parents? Or professionals? How can these differing sets of needs be met?Margaret Henry proposes three dimensions of caregiving behaviour through which parents and professionals not only help young children to develop, but can also help one another's development. Evi.